2003
DOI: 10.1080/02813430310001734
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with high prescribing of benzodiazepines and minor opiates

Abstract: Emotional and relational aspects play an important part in decisions on prescribing benzodiazepine and minor opiates. Our findings indicate that there is potential for improvement in prescribing practice; for instance, by investigating how and to what extent prescribing decisions are influenced by patients and how the difficulties experienced influence the decision process. Better practice routines could be considered such as not prescribing these drugs without consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…In contrast to studies on chronic usage, which have shown that patient demand was perceived to be a strong influencing factor for prescribing [16,38], GPs did not mention this as an element to initiate BZD treatment. The patient's demand might be a typical element of chronic usage due to the addictive nature of the drug once it has been introduced to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to studies on chronic usage, which have shown that patient demand was perceived to be a strong influencing factor for prescribing [16,38], GPs did not mention this as an element to initiate BZD treatment. The patient's demand might be a typical element of chronic usage due to the addictive nature of the drug once it has been introduced to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have covered GPs' or psychiatrists' attitudes to and prescribing of BZD anxiolytics, BZD hypnotics and/or z-hypnotics (20,(58)(59)(60)(61)(62). At the time of initiating BZD prescription, some GPs seem to feel overwhelmed by the psychosocial problems of patients, and find BZDs to be "the lesser evil" (58).…”
Section: Antidepressantsmentioning
confidence: 99%
“…This is partly explained by an increasing population, with an average growth per year of 0.4-0.5% since 1991 and an increasing proportion of older people. 8 Previous research has documented the attitudes of patients and doctors to benzodiazepines, [9][10][11][12][13][14][15] but little has so far been published about their perceptions or experiences of Z drugs, either alone or compared with benzodiazepine hypnotics. Studies of benzodiazepine hypnotics have shown that patients believe that they are more effective and safer than do doctors.…”
mentioning
confidence: 99%